2017
DOI: 10.21089/njhs.23.0116
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Regenerative Medicine: Prospects and Pitfalls

Abstract: Stem cells are the cells that have the ability to regenerate themselves and are able to differentiate into one or more specialized cell types. This unique property makes them a valuable source for in vitro disease modeling, drug designing, regenerative medicine and tissue engineering. As no specie can fully mimic the human microenvironment, human cell models derived from patients cells provide a fascinating avenue for enhancing our current understanding of the early molecular stages of various diseases followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…The potentials for stem cells are being explored currently but to date, the few safe and efficacious options for clinical applications are mainly limited to haematopoietic stem cell transplantation for some malignant and some non-malignant hematologic conditions (Zehravi et al, 2017). The journey from bench to the bedside is long, arduous and regulated for the sake of science, its researchers and the patients alike.…”
Section: Approved Stem Cell Based Interventions For Clinical Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…The potentials for stem cells are being explored currently but to date, the few safe and efficacious options for clinical applications are mainly limited to haematopoietic stem cell transplantation for some malignant and some non-malignant hematologic conditions (Zehravi et al, 2017). The journey from bench to the bedside is long, arduous and regulated for the sake of science, its researchers and the patients alike.…”
Section: Approved Stem Cell Based Interventions For Clinical Applicationmentioning
confidence: 99%
“…Many clinical trials at different phases are underway for SCI and can be found listed at online registry sites like the United States' National Library of Medicine's clinicaltrials.gov, European Union's EU Clinical Trials Register (EU-CTR), United Kingdoms' ISRCTN registry, Australian New Zealand Clinical Trials Registry (ANZCTR), etc. (Health 2012; Zehravi et al, 2017).…”
Section: Approved Stem Cell Based Interventions For Clinical Applicationmentioning
confidence: 99%